Analysis of the Enforcement of the Survival Clause for Foreign Investors in Indonesia Due to the Termination of the Bilateral Investment Treaty (BIT) - Hana Pertiwi (Publikasi Indonesia, 2024)
This analysis examines the legal consequences of Indonesia's termination of the Bilateral Investment Agreement (BIT) on foreign investment entering or planning to enter Indonesia after the termination date. Bilateral Investment Agreements or BITs are known as a legal umbrella for foreign investors investing in host countries, including legal protection for foreign investors in Indonesia. The Indonesian government has signed BITs with several other countries to strengthen cooperation in the investment sector. However, because the contents of the agreement are no longer to the country's development and the current investment climate and limit Indonesia's policy space in regulating matters related to the protection of national interests, Indonesia has ended many BITs. The consequence of Indonesia's termination of the BIT for foreign investors is that there is the potential for investment disputes to arise. In this situation, the provisions of the survival clause will apply to foreign investments made before the termination date, because even though the BIT has ended, there is a certain period for the BIT to still be valid for investments made before the end of the agreement period so that in other words the agreement remains effective in protecting investors from both countries who previously existed or who had carried out restructuring before the termination date of the BIT. For foreign investments that enter or will enter Indonesia after the termination date, protection can be obtained by creating a new BIT or through a Multilateral Investment Treaty (MIT) and Free Trade Agreement (FTA) where Indonesia as the Host Country is a party to the agreement.